Trends of 5-Aminosalicylate Medication Use in Patients With Crohn Disease. Issue 4 (29th May 2020) - Noureldin, Mohamed; Cohen-Mekelburg, Shirley; Mahmood, Asadullah; Stidham, Ryan; Higgins, Peter D R; Govani, Shail; Deshpande, Amar R; Waljee, Akbar K
Abstract: Background: 5-aminosalicylate (5-ASA) medications have a long history of use for the treatment of inflammatory bowel disease and continue to be widely prescribed today. The effectiveness of 5-ASAs in ulcerative colitis is clear; however, studies have shown little benefit for induction or maintenance treatment of Crohn disease (CD). We aimed to quantify usage and examine trends in 5-ASA prescription rates in patients with CD. Methods: Using a retrospective design, we queried a national database of commercially insured patients (Truven-Health databases) between 2009 and 2014 to identify patients with CD aged 18 to 65 years. Prescription rates for 5-ASA medications including sulfasalazine, mesalamine, olsalazine, and balsalazide were calculated for each calendar year. Regression models were used to examine year-to-year trends in prescription rates and identify patient factors associated with 5-ASA use. Results: We identified 132, 804 patients with CD, of whom 37.3% (n = 49, 529) received a 5-ASA prescription during the study period. From 2009 to 2014, the overall prescription rates of 5-ASAs declined from 42.9% to 30.0% ( P < 0.001). Patient factors independently associated with 5-ASA use included younger age, male sex, multimorbidity, and a health maintenance organization insurance plan, while controlling for the region of residence. Conclusions: About 1 in 3 privately insured patients with CD received 5-ASA prescriptions despite their questionable effectiveness; however, in an encouraging trend, prescription rates significantly decreased from 2009 to 2014. This high prescription rate may reflect a gap in providers' knowledge regarding the available evidence—an opportunity for cost savings with improved health care delivery.